Self-powered copper sulfide/silicon heterojunction photodetectors with high-photoresponse performance - Der-Yuh Lin; Yu-Tai Shih; De-Jin Qiu; Yee-Mou Kao; Chia-Feng Lin; Sheng-Beng Hwang; Ming-Cheng Kao (APL Materials)
Impressively high-photoresponse performance was observed from copper sulfide/silicon heterojunction photodetectors, which were fabricated by chemical vapor depositing (CVD) p-type copper sulfide (CuxS) thin films onto n-type Si substrates. This CVD technique, being facile, cost-effective, low-temperature, and scalable, provides a reliable method for large-scale production. The CuxS films had desirable crystalline quality with a crystal structure of hexagonal covellite belonging to the P63/mmc space group. Temperature-dependent I–V measurements showed that the CuxS thin films behave as a degenerate semiconductor, and the p-CuxS/n-Si heterojunctions resembled a Schottky diode. The energy band diagrams of the p-CuxS/n-Si heterojunctions depicted a Schottky barrier of 1.52 eV and a built-in voltage of 1.27 V within the depletion region. The power conversion efficiency (PCE) of the p-CuxS/n-Si heterostructures was determined to be 2.52%. Thus, as photovoltaic devices, the PCE exceeded the reported values for CuO/Si, Cu2O/Si, and Cu2Se/Si systems. Analysis of the photoelectric properties showed that the p-CuxS/n-Si photodetectors have a good self-powered attribute, displaying rapid, reproducible, sensitive, and robust photoresponse performance. Furthermore, the Si substrate causes simplification in coupling with well-developed Si electronics. Thus, p-CuxS/n-Si heterojunction photodetectors are promising for applications in optoelectronics.